ANALYSIS OF COMMUNITY HEALTH VOLUNTEER (CHV) BEHAVIOR IN DETECTING PRESUMPTIVE PULMONARY TB IN BANJARNEGARA: Analisis Perilaku Kader Kesehatan dalam Penemuan Suspek TBC Paru di Kabupaten Banjarnegara - Saroh, Saroh; Widjanarko, Bagoes; Shaluhiyah, Zahroh (Jurnal Berkala Epidemiologi, 2025)
Background: Pulmonary TB case detection in Banjarnegara Regency from 202 to 2023 has fallen short of the target. As of June 2024, only 21% of suspected pulmonary TB cases have been identified. The behavior of community health volunteers (CHV) who actively seek out TB cases in the community starting from conducting visits, providing basic education to at least 20 close contacts of the index TB case, screening symptoms through interviews using the National TB 16K form, to encouraging symptomatic contact to undergo sputum examination at the health center is closely linked to the detection of pulmonary presumptive TB. Purpose: To analyze the behavior of CHV and to identify the factors influencing CHV behavior to identify presumptive TB pulmonary.   Methods: The research design used was quantitative with a cross-sectional and observational design. The sampling technique used was total sampling with a total of 136 respondents. Results: Based on research conducted, 77 demonstrated good behavior in presumptive identification, while 59 exhibited less favorable behavior. The majority of respondents had excellent knowledge (92.65%), a supportive attitude towards presumptive detection (65.44%), and good motivation (60.29%). There is a relationship between knowledge (P=0.015), attitude (P=0.006), and motivation (P=0.000) with the behavior of community health volunteers in identifying pulmonary TB presumptive in Banjarnegara Regency. Conclusion: 56.62% of respondents exhibited good behavior in detecting pulmonary TB presumptives. Further training with an interactive learning approach is necessary to enhance the capacity of community health volunteers.